Accessory sulci and segmentation on the surface of the liver: a clinical pitfall - Deshmukh, Vishwajit Ravindra; Seth, Suryakanta; Sahni, Chetan (International Journal of Research in Medical Sciences, 2017)
Diaphragmatic surface of liver is usually smooth but sometimes it is well marked by the sulci or indentations. Sometimes these sulci were so deep to be termed as fissures as they divide the lobe of liver into different segments. We report the case of accessory sulci along the Anterosuperior surface of the right lobe associated with Reidel’s lobe along the inferior border of the left lobe of same specimen. In another specimen, the sulci were so deep to be termed as fissures, which divides the caudate and quadrate lobe. Knowledge about the accessory sulci and lobes were necessary as they may appear as incidental finding during the laparoscopic examinations. Hence, it is very much promising to know about these sulci and lobes for hepatobiliary surgeons, anatomists and radiologists.